Analysis of Trans Fatty Acid Content in Snacks and Non-Dairy Creamers by Attenuated Total Reflection Fourier Transform Infrared Spectroscopy - Suwannakood, Waraporn; Patarapanich, Chamnan; Tongyonk, Linna (Journal of Health Research, 2017)
Trans fats are found mostly in products which contain partially hydrogenated vegetable oils in manufacturing process such as bakery products, deep fried foods, margarine and shortening. Snacks and non-dairy creamers contain partially hydrogenated vegetable oils but trans fat content of them have a few report. Therefore, the aim of this study was to determine trans fat content in six groups of snacks including crackers, stick biscuits (Kha-Kai), potato chips, biscuits, microwave popcorns, wafers and twelve brands of non-dairy creamers. All samples were selected from supermarket in Bangkok during October 2009 to January 2010. Trans fat levels were determined by the attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR) with negative second derivative mode. The highest of trans fat content found in the microwave popcorn was 6.23 g/ 100 g food (0.90-9.96 g/100 g food), following by wafer;1.25 g/ 100 g food (0.00-3.65 g/100 g food), biscuits; 0.81 g/100 g food (0.04-2.31 g/100 g food), crackers; 0.05 g/100 g food (ND-0.05 g/100 g food), potato chip; 0.01 g/100 g food (ND-0.01 g/100 g food) and stick biscuits (Kha-Kai) was not detected. Twelve brands of non-dairy creamers contained trans fat. Trans fat contents of two brands which contained soybean oil were range 10.29-14.62 g/100 g food or 0.31-0.44 g/serving size while ten brands which contained palm kernel oil were range 0.17-0.70 g/100 g food or 0.01-0.02 g/serving size. Although, the finding show that the amount of trans fat in samples were low however, consumers should be aware the harmful effect of trans fat. In the future, FDA should inquire trans fat contents on nutrition label and consumers should be educated about health effect of trans fat for minimized the cardiovascular risks associated with trans fat.